2023
DOI: 10.1163/15685403-bja10266
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the actinomycete, Nocardiopsis, from Haizhou Bay, and its application as a probiotic for Exopalaemon carinicauda (Holthuis, 1950) (Caridea, Palaemonidae)

Abstract: Actinomycetes, as the main producers of a variety of active metabolites and enzymes, have received extensive attention in aquaculture. An actinomycete had been isolated from Haizhou Bay and been identified by morphological analysis and 16S rRNA sequencing. Results showed that the actinomycete had the highest similarity (99.65%) with Nocardiopsis sp. and was named strain E10. Strain E10 produced an exo-enzyme with proteinase effect that showed strong antibacterial activity against Vibrio anguillarum. This strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Targeted gene expression analyses in green shore crab (Carcinus maenas) gill tissue reported that genes involved in acid-base regulation are affected by high pCO 2 [39,40]. Transcriptome-wide expression analysis identified changes in genes involved in energy metabolism and apoptosis activity in shrimp (Exopalaemon carinicauda) [41], and immune functions, energy metabolism, and ion transport in the Chinese mitten crab (Eriocheir sinensis) [42,43]. Metabolomic analyses in juvenile Dungeness (Cancer magister) and green shore (Carcinus maenas) crabs both found amino acid metabolism to respond to acidified conditions, perhaps due to increased buffering needs [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted gene expression analyses in green shore crab (Carcinus maenas) gill tissue reported that genes involved in acid-base regulation are affected by high pCO 2 [39,40]. Transcriptome-wide expression analysis identified changes in genes involved in energy metabolism and apoptosis activity in shrimp (Exopalaemon carinicauda) [41], and immune functions, energy metabolism, and ion transport in the Chinese mitten crab (Eriocheir sinensis) [42,43]. Metabolomic analyses in juvenile Dungeness (Cancer magister) and green shore (Carcinus maenas) crabs both found amino acid metabolism to respond to acidified conditions, perhaps due to increased buffering needs [44,45].…”
Section: Introductionmentioning
confidence: 99%